Becoming-animal in the Chinese Martial Arts - Farrer, Douglas (Living Beings, 2020)
This chapter examines Chow’s Family Southern Praying Mantis to delineate a field of action involving animals and humans, where humans develop secret powers of the body derived from observation and self-experimentation combined with centuries of embodied—not just oral—transmission. For Deleuze and Guattari becoming is rhizomic; it does not depend on systems of a scientific classification or genealogy. Martial performance ethnography is where the researcher joins in and learns a martial art. Chow Gar comprises a method for the development and transmission of deadly martial skills. Legend has it that Chow Gar emerged from the Fukien Shaolin Temple, which was destroyed when the monks became involved in the revolutionary uprisings against the Ming Dynasty. Chow Gar develops the hidden or dark powers including sharp eyesight, strong bones, iron fingers, flexible sinews and extraordinary strength, all trained through sweat, blood and breath. According to oral history, Wong Fook Go possessed black fingertips like steel talon

Brazilian jiu-jitsu is therapy. Shifting subjectivities on Guam - Farrer, Douglas (Etnografia e ricerca qualitativa, 2019)

Captivation, false connection and secret societies in Singapore - Farrer, Douglas (2018)
Interminable ritual repetition of set movements (taolu) has resulted in Chinese martial arts facing trenchant criticism as being useless in fight sports, mixed martial arts, and actual combat. In Singapore, the neglect of body-callousing or conditioning methods in Chinese martial arts may render them unfit for unarmed combat. This led me to ask whether the entire edifice of set practice in the martial arts is based upon a false connection. Researching Hong Shen Choy Li Fut, a Chinese fighting style notoriously infested with gangsters in the red-light district of Singapore, I was informed that all Chinese martial arts and lion dance associations are triads. Nevertheless, even here I was shown curious dancelike interpretations for martial arts moves taught. Does the endless repetition of sets captivate the performer into a delusional belief that they are becoming a better fighter? Are the audiences of such sets, performed in dramatic rendition, similarly held captive in a false connection?.
Created from Fastlane, Scopus look-up
Keywords: Captivation; Chinese martial arts; combat; false connection; performance; psychoanalysis; Singapore; taolu; triads

Chants of re-enchantment: Chamorro spiritual resistance to colonial domination - Farrer, Douglas S.; Sellmann, James D. (Social Analysis, 2014)
The Chamorro people inhabit an archipelago known as the Mariana Islands located in the western Pacific Ocean. Seventeenth-century Chamorros took ancestral skulls into warfare against the Spanish in the period of the Spanish conquest. The possession of such skulls manifested profound symbolic power. In the aftermath of the war, the survivors converted to Catholicism, amalgamating their ancient religious practices with that faith. Resistance through the centuries against Spanish, Japanese, and American colonial power has been anchored in Chamorro cultural continuity, albeit in an ostensibly fragmented and augmented form. A site of strategic US military bases, Guam now anticipates further military build-up. War magic and warrior religion are lenses that enable the study of colonial domination where the battle lines fault across military, economic, and political frames toward cultural fronts. © Berghahn Journals.
Created from Fastlane, Scopus look-up
Keywords: Chant; Enchantment; Guam; Magic; Performance; Religion; Taotaomo'na; Warfare

Coffee-shop gods: Chinese martial arts of the Singapore diaspora - Farrer, Douglas (Martial Arts as Embodied Knowledge: Asian Traditions in a Transnational World, 2011)

'Deathscapes' of the Malay martial artist - Farrer, Douglas (Social Analysis, 2006)
This article traces the connections between death and the afterlife as configured through the Malay martial art silat in Malaysia, Singapore, and the Riau Archipelago. The practice and performance of silat are addressed here through aspects of non-material and material culture, including ritual, dance, jewelry, symbols, and art. Silat is designed to transform physically and spiritually the silat practitioner and to remove the fear of death and dying. This transformation is partly accomplished by summoning (berseru) the shadows of the 'potent dead'. However, the contemporary medicalization of death may preclude the possibility of a 'noble death'. To illustrate the disjuncture of 'deathscapes', I compare the agonizing death of a silat master to the cemetery ordeal of his son. © Berghahn Journals.
Created from Fastlane, Scopus look-up
Keywords: 'Deathscapes'; 'Noble death'; Malay martial arts; Silat; Urobos; War magic; Warrior shaman

Dreamwork, art worlds and miracles in Malaysia - Farrer, Douglas S. (World Art, 2020)
Dreamwork recorded in the Malay art world questions the occult power of artistic agency. As I did participant observation in Malaysia and Singapore, the artist Mohammad Din Mohammad divulged knowledge of Sufi lore, shamanic healing, and Malay martial arts (silat). On a quest to comprehend, discover, create and articulate esoteric skills, secret knowledge and mysterious artifacts, the artist produced fine art paintings, talismanic jewelry and assemblage sculptures. These were to be used in psychic defence, dream incubation, for inspiration, and as medicine. A field site discussion as to whether a reported vision of a mysterious shadow warrior is a true, false, or meaningless dream forms the kernel of a dreamwork dialogue regarding miraculous agency. The artwork raises questions pertaining to sorcery, Islam, agency, and power in Southeast Asia, revealing a political battle of Sufi versus Wahhabi notions in the constitution of Malay modernity.
Created from Fastlane, Scopus look-up
Keywords: agency; art worlds; dreamwork; healing; miracles; power

EFFICACY AND ENTERTAINMENT IN MARTIAL ARTS STUDIES anthropological perspectives - Farrer, Douglas S. (Martial Arts Studies, 2015)
Martial anthropology offers a nomadological approach to Martial Arts Studies featuring Southern Praying Mantis, Hung Sing Choy Li Fut, Yapese stick dance, Chin Woo, Brazilian jiu-jitsu, and seni silat to address the infinity loop model in the anthropology of performance/performance studies which binds together efficacy and entertainment, ritual and theatre, social and aesthetic drama, concealment and revelation. The infinity loop model assumes a positive feedback loop where efficacy flows into entertainment and vice versa. The problem addressed here is what occurs when efficacy and entertainment collide? Misframing, captivation, occulturation, and false connections are related as they emerged in anthropological fieldwork settings from research into martial arts conducted since 2001, where confounded variables may result in new beliefs in the restoration of behaviour.
Created from Fastlane, Scopus look-up
Keywords: Brazilian jiu-jitsu; Chinese martial arts; Efficacy; entertainment; nomadology; performance; seni silat

Introduction: Cross-cultural articulations of war magic and warrior religion - Farrer, Douglas S. (Social Analysis, 2014)
Previous anthropology emphasized symbolic incantations at the expense of the embodied practice of magic. Foregrounding embodiment and performance in war magic and warrior religion collapses the mind-body dualism of magic versus rationality, instead highlighting social action, innovation, and the revitalization of tradition, as tempered historically by colonial and post-colonial trajectories in societies undergoing rapid social transformation. Religion and magic are re-evaluated from the perspective of the practitioner's and the victim's embodiment in their experiential life-worlds via articles discussing Chinese exorcists, Javanese spirit siblings, Sumatran black magic, Tamil Tiger suicide bombers, Chamorro spiritual re-enchantment, tantric Buddhist war magic, and Yanomami dark shamans. Central themes include violence and healing, accomplished through ritual and performance, to unleash and/or control the power of gods, demons, ghosts and the dead. © Berghahn Journals.
Created from Fastlane, Scopus look-up
Keywords: Embodiment; Magic; Performance; Shamanism; Sorcery; Violence; Warfare; Witchcraft

Martial Arts as Embodied Knowledge: Asian Traditions in a Transnational World - Whalen-Bridge, John; Farrer, Douglas (State University of New York Press, 2011)
A wide-ranging scholarly consideration of the martial arts. This landmark work provides a wide-ranging scholarly consideration of the traditional Asian martial arts. Most of the contributors to the volume are practitioners of the martial arts, and all are keenly aware that these traditions now exist in a transnational context. The book’s cutting-edge research includes ethnography and approaches from film, literature, performance, and theater studies. Three central aspects emerge from this book: martial arts as embodied fantasy, as a culturally embedded form of self-cultivation, and as a continuous process of identity formation. Contributors explore several popular and highbrow cultural considerations, including the career of Bruce Lee, Chinese wuxia films, and Don DeLillo’s novel Running Dog. Ethnographies explored describe how the social body trains in martial arts and how martial arts are constructed in transnational training. Ultimately, this academic study of martial arts offers a focal point for new understandings of cultural and social beliefs and of practice and agenc

Performance Ethnography - Farrer, Douglas (Martial Arts Studies: a Reader, 2018)

Shadows of the Prophet - Farrer, Douglas (Springer Nature, 2009)
This is the first in-depth study of the Malay martial art, silat, and the first ethnographic account of the Haqqani Islamic Sufi Order. Drawing on 12 years of research and practice in Malaysia, Singapore, and England, social anthropologist and martial arts expert D.S. Farrer considers Malay silat through the transnational Sufi silat group called Seni Silat Haqq, an off-shoot of the Haqqani-Naqshbandi Sufi Order. This account combines theories from the anthropology of art, embodiment, enchantment, and performance to show how war magic and warrior religion amalgamate in traditional Malay martial arts, where practitioners distance themselves from “becoming animal” or going into trance, preferring a practice of spontaneous bodily movement by summoning the power of Allah. Silat and Sufism are revealed through the social dramas of 40-day boot-camps where Malay and European practitioners endeavor to become shadows of the Prophet, only to have their faith tested through a ritual ordeal of boiling oil. The unseen realm and magical embodiment is further approached through an account of Malay deathscapes where moving through the patterns of silat summons the spirits of ancestral heroes. Those interested in Malaysia, Sufism, transnational Islam, and the study of religion, conversion, magic, sorcery, theatre and martial arts will find this book indispensable. "the eagerly awaited monograph on the practice of silat" Joel S. Kahn "No other work on silat has achieved this level of inside understanding" Roxana Waters
Keywords: Anthropology; Europe; Haqqani-Naqshbandi; Islam; Martial arts; Nation; Performance studies; Phenomenology; Religion; Silat; Sociology of religion; Southeast Asia; Sufism; Transnational; War magic

The healing arts of the Malay mystic - Farrer, Douglas (Journal of Visual Anthropology, 2008)
The legacy of Alfred Gell offers a rich stock of ingenious ideas to apply and extend to the thought-provoking artwork of Mohammad Din Mohammad, who combines the skills (ilmu) of the Malay martial art silat with the knowledge of the traditional Malay healer, to press life, breath, and divine power into his painting and sculpture. The artist's agency is said to open a gateway to the unseen realm. By painting calligraphic motifs derived from the Quran with his bare hands, the artist channels Allah's energy from within, energy that is embodied and suspended within his artworks, to protect the patient from spiritual attack. The artwork serves as a protective talisman during spiritually vulnerable moments, such as birth, marriage, fasting, and death. During crisis, the power stored within the artwork may be unleashed to counter attacks from ghosts, vampires, or other nefarious creatures © 2008 by the American Anthropological Association.
Created from Fastlane, Scopus look-up
Keywords: Agency; Calligraphy; Enchantment; Silat; Sufism

The Performance of Enchantment and the Enchantment of Performance in Malay Singapore - Farrer, Douglas (Moussons : Recherche en Sciences Humaines sur l’Asie du Sud-Est, 2012)
Ab den 1960er Jahren waren die Malaien Singapurs gezwungen, aus ihren traditionellen Dörfern ( Kampung ) in „moderne“ Betongebäude umzusiedeln. Ihre ursprünglichen Dörfer – bestehend aus Holzhäusern auf Stelzen – wurden abgerissen und durch dauerhafte Sozialwohnungen ersetzt, begleitet von einer rigorosen Quotenpolitik, die repräsentativ für die multiethnische Zusammensetzung Singapurs ist. Diese Zwangsumsiedlung wurde von der Regierung und den Medien als Fortschritt dargestellt. Jetzt kommen Menschen, die von den Bewohnern dieser Dörfer abstammen, wieder zu malaiischen Hochzeiten zusammen, die regelmäßig auf der ganzen Insel stattfinden. Diese Hochzeiten finden unter den riesigen Gebäuden statt, in einem Gemeinschaftsraum, in dem die Chinesen auch ihre Beerdigungen organisieren. Hochzeits-Silat, eine malaiische Kampfkunst, die bei Hochzeiten getanzt wird, ist ein Zusammenführungsritus, der darauf abzielt, neue Familienmitglieder willkommen zu heißen und den Aufbau neuer, erweiterter Verwandtschaftsbeziehungen zu markieren. Das Tragen des Hochzeitssilats beleuchtet die Leistung im Verhältnis zu traditionellen und modernen Machtstrukturen. Angesichts der beträchtlichen Entwicklung des Utilitarismus in Singapur, des physischen Aussterbens der Kampung , der Islamisierung der Malaysier und des allgemeinen Unbehagens der gegenwärtigen nostalgischen Ernüchterung gibt die Silat -Darbietung den Malaysiern die Kraft, ihre Welt neu zu verzaubern. In diesem Prozess, der die malaiische Identität sichert, bewahrt und schafft, bringen rituelle Darbietungen die verstreute Minderheitengemeinschaft in einem wiederhergestellten Raum, einem virtuellen Kampung , zusammen
Keywords: Ästhetik; Agentur; Kunst; Kampung; Ritual; Hochzeitssilat

War Magic - Farrer, Douglas S. (Berghahn Books, 2016)
This compelling volume explores how war magic and warrior religion unleash the power of the gods, demons, ghosts, and the dead. Documenting war magic and warrior religion as they are performed in diverse cultures and across historical time periods, this volume foregrounds embodiment, practice, and performance in anthropological approaches to magic, sorcery, shamanism, and religion. The authors go beyond what magic ‘represents’ to consider what magic does. From Chinese exorcists, Javanese spirit siblings, and black magic in Sumatra to Tamil Tiger suicide bombers, Chamorro spiritual re-enchantment, tantric Buddhist war magic, and Yanomami dark shamans, religion and magic are re-evaluated not just from the practitioner’s perspective but through the victim’s lived experience. These original investigations reveal a nuanced approach to understanding social action, innovation, and the revitalization of tradition in colonial and post-colonial societies undergoing rapid social transformati